UJI AKTIVITAS PENURUNAN KOLESTEROL PRODUK MADU HERBAL YANG BEREDAR DI PASARAN PADA TIKUS PUTIH DIET LEMAK TINGGI - Ni Putu Ariantari; Sagung Chandra Yowani; Dewa Ayu Swastini (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
The research aims to investigate hypocholesterolemic activity of two marketed herbal honey products forhypocholesterolemia, mentioned as product A and B on Wistar albino rats with hypercholesterolemic diet.Hypocholesterolemic activity test was conducted with Enzymatic Photometric Test CHOD-PAP (CholesterolOxidase Phenol Aminoantipyrin) method. The result revealed that product A administered orally to Wistar albino ratswith hypercholesterolemic diet, at 0.15 mL/200g BW dose once daily, did not show hypocholesterolemic activity. Onthe other hand, product B at 0.5 mL/200g BW dose showed hypocholesterolemic activity similar to simvastatin.